2019
DOI: 10.1038/s41929-019-0328-1
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst deactivation via decomposition into single atoms and the role of metal loading

Abstract: In the high-temperature environments needed to perform catalytic processes, supported precious metal catalysts severely lose their activity over time. Even brief exposure to high temperatures can lead to significant losses in activity, which forces manufacturers to use large amounts of noble metals to ensure effective catalyst function for a required lifetime. Generally, loss of catalytic activity is attributed to nanoparticle sintering, or processes by which larger particles grow at the expense of smaller one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
206
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(216 citation statements)
references
References 44 publications
8
206
1
1
Order By: Relevance
“…Prior studies have demonstrated that the interface between metal nanoparticles and the metal oxide support can affect chemical behavior by the creation of specific active sites [12][13][14][15][16][17][18] and direct migration or "spillover" 19 of reactive species created on one phase to a neighboring phase of differing reactivity [19][20][21][22][23][24][25] . The metal/oxide support interface can significantly restructure in reactive gas environments on a short timescale of minutes and long length scales of microns 26 . Catalyst activity can be significantly modified by interface restructuring including changes in coordination environment 27 , catalyst encapsulation 28 , and metal component transport and alloying [29][30][31][32][33] .…”
mentioning
confidence: 99%
“…Prior studies have demonstrated that the interface between metal nanoparticles and the metal oxide support can affect chemical behavior by the creation of specific active sites [12][13][14][15][16][17][18] and direct migration or "spillover" 19 of reactive species created on one phase to a neighboring phase of differing reactivity [19][20][21][22][23][24][25] . The metal/oxide support interface can significantly restructure in reactive gas environments on a short timescale of minutes and long length scales of microns 26 . Catalyst activity can be significantly modified by interface restructuring including changes in coordination environment 27 , catalyst encapsulation 28 , and metal component transport and alloying [29][30][31][32][33] .…”
mentioning
confidence: 99%
“…It can be seen that the crystallinity of the inlet region was highest, followed by the outlet region and the middle region was the smallest. The increase of crystallinity is mainly caused by the sintering of noble metals and metal oxides and the formation of agglomerates with poor crystalline phase 40 .
Figure 11 Crystallinity of the inlet, middle and outlet regions of CDPF after aging.
…”
Section: Resultsmentioning
confidence: 99%
“…Similar to independent catalysis of CO oxidation and NO reduction, both CO and NO could easily be eliminated from gasoline-fueled engine exhaust systems by SACs [58,65,66]. However, the usefulness of SACs and small clusters with ensemble sites catalysts have been the debate for HC (CH4, C3H6 and C3H8) oxidation [56,58,66,128].…”
Section: Three-way Catalytic and Diesel Oxidation Catalytic Reactionmentioning
confidence: 99%